Development of Transportation Planning: A Systematic Literature Review of Methods - Sumantri, Vena Nuri; Dwiani, Nurmala; Rachman, M. Nanda Fajar Arij; Rijaluddin, Arief; Rifai, Andri Irfan (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
Transportation planning plays a principal role in sustainable development, but many regions still face problems such as congestion and high emissions. This study uses a systematic literature review (SLR) method to analyse the development of transportation planning techniques based on publications indexed by Google Scholar. The prime focus is on the trend of data-based approaches and technology integration. The results show that the dominant topics include regulation, planning, transportation planning, and accidents. The largest publisher is Elsevier, followed by Springer and Taylor & Francis, indicating the dominance of high-reputation journals. The types of sources vary, with the majority coming from the “Other” category and books. Publications increased significantly in 2009–2010 and decreased in the last decade. This study provides a comprehensive overview of the main directions and focuses of transportation research and serves as a basis for further studies.